Genome-wide association study of Nelore and Angus heifers with low and high ovarian follicle counts - Loureiro, Bárbara; Ereno, Ronaldo Luiz [UNESP]; Pupulim, Antônio Guilherme Roncada [UNESP]; Tramontana, Maria Clara Viana Barroso; Tabosa, Henrique Passos; Barros, Ciro Moraes [UNESP]; Favoreto, Maurício Gomes [UNESP] (My University, 2024)
The number of antral follicles is considered an important fertility trait because animals with a high follicle count (HFC) produce more oocytes and embryos per cycle. Identification of these animals by genetic markers such as single nucleotide polymorphisms (SNPs) can accelerate selection of future generations. The aim of this study was to perform a genome wide association study (GWAS) on Nelore and Angus heifers with HFC and low (LFC) antral follicle counts. The groups HFC and LFC for genotyping were formed based on the average of total follicles (≥ 3 mm) counted in each breed consistently ± standard deviation. A total of 72 Nelore heifers (32 HFC and 40 LFC) and 48 Angus heifers (21 HFC and 27 LFC) were selected and the DNA was extracted from blood and hair bulb. Genotyping was done using the Illumina Bovine HD 770K BeadChip. The GWAS analysis showed 181 and 201 SNPs with genotype/phenotype association (P ≤ 0.01) in Nelore and Angus heifers, respectively. Functional enrichment analysis was performed on candidate genes that were associated with SNPs. A total of 97 genes were associated to the 181 SNPs in the Nelore heifers and the functional analysis identified genes (ROBO1 and SLIT3) in the ROBO-SLIT pathway that can be involved in the control of germ cell migration in the ovary as it is involved in lutheal cell migration and fetal ovary development. In the Angus heifers, 57 genes were associated with the 201 SNPs, highlighting Fribilin 1 (FBN1) gene, involved in regulation of growth factors directly involved in follicle activation and development. In summary, GWAS for Nelore and Angus heifers showed SNPs associated with higher follicle count phenotype. Furthermore, these findings offer valuable insights for the further investigation of potential mechanism involved in follicle formation and development, important for breeding programs for both breeds.
Keywords: Bovine HD 770 K SNP; candidate genes; follicle; reproduction; SNPs